2013
DOI: 10.1007/s00248-013-0287-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Structure in the Rhizosphere of a Cry1Ac Bt-Brinjal Crop and Comparison to Its Non-transgenic Counterpart in the Tropical Soil

Abstract: To elucidate whether the transgenic crop alters the rhizospheric bacterial community structure, a 2-year study was performed with Cry1Ac gene-inserted brinjal crop (Bt) and their near isogenic non-transformed trait (non-Bt). The event of Bt crop (VRBT-8) was screened using an insect bioassay and enzyme-linked immunosorbent assay. Soil moisture, NH4 (+)-N, NO3 (-)-N, and PO4 (-)-P level had non-significant variation. Quantitative polymerase chain reaction revealed that abundance of bacterial 16S rRNA gene copie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…reported that soil MBC was inhibited by transgenic cotton proteins compared to their non-transgenic controls. Similarly, Singh et al (2013b) reported that MBC was slightly reduced in the transgenic brinjal soils, and the overall impact of transgenic brinjal was lower than nontransgenic brinjal due to seasonal changes (Singh et al 2013b). Contrarily, higher amounts of MBC under various Bt-cotton and bulk soils were found in Indian Vertisols than non-Bt cotton soils (Velmourougane & Sahu 2013).…”
Section: Effect Of Bt-cotton On Soil Microbial Biomass Carbon and Soimentioning
confidence: 95%
“…reported that soil MBC was inhibited by transgenic cotton proteins compared to their non-transgenic controls. Similarly, Singh et al (2013b) reported that MBC was slightly reduced in the transgenic brinjal soils, and the overall impact of transgenic brinjal was lower than nontransgenic brinjal due to seasonal changes (Singh et al 2013b). Contrarily, higher amounts of MBC under various Bt-cotton and bulk soils were found in Indian Vertisols than non-Bt cotton soils (Velmourougane & Sahu 2013).…”
Section: Effect Of Bt-cotton On Soil Microbial Biomass Carbon and Soimentioning
confidence: 95%
“…Considerable previous work has been done in terms of biosafety on the soil enzyme and/or microbial community structure of cry1Ac transgene crops, including cry1Ac transgenic cotton (Shen et al, 2006 ; Zhang et al, 2015 ), cry1Ac transgenic brinjal (Singh et al, 2013 ), and cry1Ac transgenic oilseed rape (Liu et al, 2015 ). Shen et al ( 2006 ) investigated the potential risk of transgenes on the soil ecosystem of cry1Ac cotton (Sukang-103) and its non- cry1Ac cotton counterpart (Sumian-12) and found that there was no evidence for any adverse effect of cry1Ac cotton on the soil ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al ( 2015 ) found that cry1Ac cotton did not show any clear effects on soil microbial communities but the microbial communities were markedly affected by the plant growth stage. Singh et al ( 2013 ) evaluated the rhizospheric bacterial community structure of cry1Ac brinjal and their near isogenic non-transformed trait and found that microbial biomass carbon showed a slight reduction in cry1Ac brinjal soils and the overall impact of c ry1Ac expressing transgenic brinjal was lower than that due to seasonal changes. Liu et al ( 2015 ) assessed the impacts of cry1Ac transgenic oilseed rape on soil nematodes and microbial communities and concluded that there was no direct effects on the rhizosphere nematode and microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al . (,c) have recently assessed the variation in actinomycetes and bacterial community in soil planted with Cry1Ac expressing Bt brinjal. However, no effort has been made to assess the effect of Bt brinjal on fungal community structure (diversity and density).…”
Section: Introductionmentioning
confidence: 99%